War - Junger, Sebastian (Twelve, 2010)
Junger, author of "The Perfect Storm," turns his brilliant and empathetic eye to the reality of combat in this on-the-ground account that follows a single platoon through a 15-month tour of duty in the most dangerous outpost in Afghanistan's Korengal Valley.